The Efficacy of Frontline Near‐Peer Teaching in a Modern Medical Curriculum. Issue 3 (17th October 2018) - Harrison, Charlotte H.; Elmansouri, Ahmad; Parton, William; Myers, Matthew A.; Hall, Samuel; Stephens, Jonny R.; Seaby, Eleanor G.; Border, Scott
Abstract : Within medical education a reduction in curriculum time for subjects, such as anatomy puts pressure on educators to ensure the same learning outcomes are conveyed in less time. This has the potential to impact negatively on student experience. Near‐peer teaching (NPT) is often praised as an effective revision tool, but its use as a frontline teaching resource remains unreported. The study explores the potential for NPT to promote delivery of learning outcomes and maximize student experience within a neuroanatomy module for second year medical students. The study occurred in three educational settings, (1) frontline NPT of cranial nerves, (2) revision session NPT of cranial nerves, and (3) NPT alongside faculty staff in laboratory‐based neuroanatomy practical exercises. For the first and second components, knowledge was measured using a pre‐ and post‐session test and student perception was ascertained with a questionnaire. For the third component, student perception was assessed with an end‐of‐module survey. The results show that overall, NPT was well received by learners. A significant knowledge gain was seen between the pre‐ and post‐session test of the frontline NPT session. The study presents evidence in favor of using NPTs to supplement the delivery of learning outcomes in a time and resource constrained curriculum. In particular, for the effective delivery of frontline material. Anat Sci Educ 0: 1–9. © 2018 American Association of Anatomists.